2010
DOI: 10.2337/dc10-s089
|View full text |Cite
|
Sign up to set email alerts
|

National Standards for Diabetes Self-Management Education

Abstract: Diabetes self-management education (DSME) is a critical element of care for all people with diabetes and is necessary in order to improve patient outcomes. The National Standards for DSME are designed to define quality diabetes self-management education and to assist diabetes educators in a variety of settings to provide evidence-based education. Because of the dynamic nature of health care and diabetes-related research, these Standards are reviewed and revised approximately every 5 years by key organizations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
324
1
31

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 335 publications
(368 citation statements)
references
References 138 publications
9
324
1
31
Order By: Relevance
“…Enhancing the message via diverse methods, such as nutrition lectures, books, newspapers, television, radio and community activities, can make patients form healthy eating habits, thus achieving optimal clinical effect. In the USA, diabetes self-management education is recommended with national standards and provided by professional diabetes educators other than physicians (12) . Data from the KAP survey showed that the patients who had diabetes education experience had significantly higher scores in knowledge, practice and total KAP than those without diabetes education experience.…”
Section: Discussionmentioning
confidence: 99%
“…Enhancing the message via diverse methods, such as nutrition lectures, books, newspapers, television, radio and community activities, can make patients form healthy eating habits, thus achieving optimal clinical effect. In the USA, diabetes self-management education is recommended with national standards and provided by professional diabetes educators other than physicians (12) . Data from the KAP survey showed that the patients who had diabetes education experience had significantly higher scores in knowledge, practice and total KAP than those without diabetes education experience.…”
Section: Discussionmentioning
confidence: 99%
“…physical activity, and medication taking has been demonstrated to improve diabetes outcomes and quality of life, and reduce the risk of complications [7][8][9], at least short term. Self-management support that includes behavioral goal setting and follow-up support is highly recommended as an effective strategy for improving chronic illness [10], but may be insufficient if not well integrated into patients' lives and reinforced through their routine diabetes care [11].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes self-management education (DSME) empowers the person with diabetes with the knowledge, skills and motivation that are needed to perform appropriate self-care (16) . DSME has been shown to be effective in improving knowledge, self-care behaviours, glycaemic control and other health outcomes (17,18) .…”
mentioning
confidence: 99%